Radiofrequency Ablation versus Resection in Large Single Nodule of Hepatocellular Carcinoma: an Evidence-based Case Report - Felix Firyanto Widjaja; Kemal Fariz Kalista; Juferdy Kurniawan (Acta Medica Indonesiana, 2019)
Background: nowadays, radiofrequency ablation (RFA) is applied widely as an alternative therapy of resection in patient with hepatocellular carcinoma (HCC). Moreover, in single nodule with size of less than 2 cm, RFA can be the primary treatment. Although resection is the main treatment and one of the curative treatments in nodule meeting Milan criteria, it needs consideritation of the surgery risk stratification. This report was aimed to search evidence of RFA compared with RFA in term of survival in patient with HCC single nodule size of more than 5 cm. Methods: the searching was done using PubMed, Scopus, Web of Science, dan CINAHL from EBSCO with keyword of “hepatocellular carcinoma”, “single nodule”, “radiofrequency ablation”, “resection”, and “survival”. The limitation of the article was English with clinical question of “In patient with HCC single nodule size of more than 5cm, was RFA more superior in resection in term of survival?”. Results: there were three articles with retrospective study. One of the article combined RFA and percutaneous ethanol injection in the analysis, meanwhile another article combined RFA and transarterial chemoembolization. These articles showed conflicting data that showed absolute risk reduction of 33% till absolute risk increment of 60.6%. Conclusion: all studies used RFA as the alternative of resection when the the tumor was irresectable which means the severity is higher in RFA group. Hence, we can not solely conclude that RFA resulted in worse survival.